Coal-Mining Safety in the Progressive Period : The Political Economy of Reform - Graebner, William (Book collections on Project MUSE., 1976)
Through the first decade of the twentieth century, Americans looked upon industrial accidents with callous disregard; they were accepted as an unfortunate but necessary adjunct to industrial society. A series of mine disasters in December 1907 (including one in Monongah, West Virginia, which took a toll of 361 lives) shook the public, at least temporarily, out of its lethargy. In this award-winning study, author William Graebner traces the development of mine safety reform in the years immediately following these tragic events.